## How to Simplify an Exponent of 0

## Examples

\[15^0=1\]

\[4^0=1\]

\[289^0=1\]

## Why It Works

When I first learned how to simplify an exponent of 0, I was really confused. I wasn’t sure how to multiply a number by itself 0 times, but I was pretty sure that 1 was NOT a logical answer.

Then I saw the following explanation and it suddenly made sense.

To see why any number with an exponent of 0 equals 1, let’s start by listing and simplifying the powers of 3…

Take a look at the pattern.

What do you notice?

What happens to the answers as the exponents get smaller?

When I look at it, I notice that it’s a geometric sequence.

Every time the exponent decreases by 1, the simplified answer is one-third of the previous term’s answer.

If we continue this pattern of dividing each term by 3 to find the next term, it suddenly becomes clear why \(3^{0}\) equals 1.

The term right before \(3^{0}\) is \(3^{1}\)(which equals 3). If you divide it by 3 to find one-third of it, you get 1. So, \(3^{0}=1\).

If you continue this pattern, you’ll see why negative exponents create fractions.

\[3^{5}= 3\times 3\times 3\times 3\times 3 = 243\]

\[3^{4}= 3\times 3\times 3\times 3 = 81\]

\[3^{3}= 3\times 3\times 3 = 27\]

\[3^{2}= 3\times 3 = 9\]

\[3^{1}= 3\]

\[3^{0}=\red{???}\]

What if you need to calculate \(4^{0}\) or \(27^{0}\) or any other number with an exponent of 0?

Well, let’s try it out with the powers of 4…

In this pattern, each term is one-fourth of the previous term. And when you divide 4 by 4, that equals 1. So, \(4^{0} = 1\).

Next, let’s try the powers of 27…

In this pattern, each term is one twenty-seventh of the previous term. And when you divide 27 by 27, you can see that \(27^{0} = 1\).

Any other number with an exponent of 0 will have a similar pattern.

So, any power with an exponent of 0 will equal 1, regardless of what number is in the base.

\[4^{5}= 4\times 4\times 4\times 4\times 4 = 1,024\]

\[4^{4}= 4\times 4\times 4\times 4 = 256\]

\[4^{3}= 4\times 4\times 4 = 64\]

\[4^{2}= 4\times 4 = 16\]

\[4^{1}= 4\]

\[4^{0}=1\]

\[28^{5}= 17,210,368\]

\[28^{4}= 614,656\]

\[28^{3}= 21,952\]

\[28^{2}= 784\]

\[28^{1}= 28\]

\[28^{0}=1\]

Fun Fact:

Some mathematicians argue that \(0^{0}\) does NOT equal 1.

It is “undefined” like \(\frac{0}{0}\).

## Negative Numbers with an Exponent of 0

\[(-12)^{0}=1\]

In this example, the negative sign is applied to the 12.

Then, the -12 is raised to an exponent of 0.

So, \((-12)^{0}\) equals positive 1.

\[-12^{0}=-1\]

In this example, 12 is the base of the power and it’s raised to an exponent of 0, which results in a positive 1.

Then, the negative sign is applied to the 1.

So, \(-12^{0}\) equals negative 1.

If you have a negative number with an exponent of 0, you have to pay attention to the parentheses.

If the negative sign is outside of the parentheses, it’s NOT part of the power and it needs to be applied AFTER the power is simplified.

If the negative sign is inside of the parentheses, then it IS part of the base of the power and it will equal a positive number when it’s raised to an even exponent.

## Constants

The constant in a polynomial is the term whose variable has an exponent of 0. A variable with an exponent of 0 can be simplified to equal 1. When you multiply that 1 by the coefficient of the term, you get a constant.

\(3x^2-5x^{1}+17x^0\)

The exponent of 0 can be simplified like this…\(17x^0=17(1)=17\).

The exponent of 1 can be simplified like this…\(-5x^1=-5x\).

So, the simplified polynomial is…

\(3x^2-5x+17\)